Degradation of adhesion between Cu and epoxy-based dielectric during exposure to hot humid environments. (November 2017) - Ahn, Key-one; Park, Se-Hoon; Kim, Young-Ho
Abstract: Degradation of adhesion between Cu and epoxy-based dielectric build-up film (EDF), which is used for fan-out wafer level packaging applications, was investigated by the reliability test. The samples were composed of four layers: epoxy molding compound substrate, laminated EDF, electroless Cu, and electrolytic Cu. Adhesion was evaluated by the 90° peel test before and after the temperature and humidity (T&H) test and the highly accelerated temperature and humidity stress test (HAST). The effects of the peel strip width and humidity exposure of the peeled edges on adhesion were determined. It was found that adhesion gradually decreased during the reliability tests. The adhesion reduction mechanism was explained by the combinatorial effect of the loss in chemical bonding and the degradation of mechanical interlocking due to moisture. A black strip was observed along the edges of the peeled Cu strips (herein referred to as the black band, BB). AES revealed the BB as the superficial oxidation of the Cu strip. HAST and the T&H test showed the effect of the BB in an additional adhesion loss. SEM revealed a local cohesive fracture of the polymer, which led to an additional loss due to an early failure of the degraded polymer. Furthermore, BB growth showed a linear correlation with the square root of time and was accompanied with adhesion reduction. Since the modern packages have micro-sized Cu lines, the formation of BB should be avoided for better reliability of devices. Highlights: Growth of discoloration at Cu strip edge under certain conditions was demonstrated. Relation between discoloration area growth and adhesion decrease is explained. Comparison between edge and non-edge area is provided using SEM and AES analysis. Difference in water diffusion path was proposed as a cause of local discoloration.